1980
DOI: 10.1111/j.1365-2141.1980.tb07181.x
|View full text |Cite
|
Sign up to set email alerts
|

Seven Pyruvate Kinase Variants Characterized by the ICSH Recommended Methods

Abstract: Seven new red-cell pyruvate kinase (PK) variants were characterized by the methods recently recommended by the International Committee for Stanardization in Haematology. The cases were all true homozygote as evidenced by consanguineous marriages of the parents; all are Japanese. These variants were designated as PK Tokyo, PK Nagasaki, PK Sapporo, PK Maebashi, PK Itabashi, PK Fukushima and PK Aizu, respectively. Low substrate affinity (high K0.5S for phosphoenolpyruvate) and thermal instability appear to play m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
20
1

Year Published

1981
1981
1996
1996

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 9 publications
2
20
1
Order By: Relevance
“…We have previously reported the clinical history and laboratory data of patients YK and FK (13). This variant enzyme was characterized by increased K0.5S (phosphoenolpyruvate), thermal instability, and slow electrophoretic mobility (13). Because the slow electrophoretic mobility of this variant PK had been demonstrated in both erythrocytes and liver (14), a structural mutation within the region common to both L-and R-type PKs was expected.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously reported the clinical history and laboratory data of patients YK and FK (13). This variant enzyme was characterized by increased K0.5S (phosphoenolpyruvate), thermal instability, and slow electrophoretic mobility (13). Because the slow electrophoretic mobility of this variant PK had been demonstrated in both erythrocytes and liver (14), a structural mutation within the region common to both L-and R-type PKs was expected.…”
mentioning
confidence: 99%
“…Here, we report the complete nucleotide sequence and the deduced amino acid sequence of human R-type PK ¶ and also present evidence of a PK variant (PK Tokyo) caused by a single amino acid substitution in R-type PK. We have previously reported the clinical history and laboratory data of patients YK and FK (13). This variant enzyme was characterized by increased K0.5S (phosphoenolpyruvate), thermal instability, and slow electrophoretic mobility (13).…”
mentioning
confidence: 99%
“…In almost all cases, family studies confirmed that variant alleles which appeared in a child were also present in the parents. One possible exception to this finding, however, is suggested by family studies of the pyruvate kinase (PK) deficiency in Japanese (Satoh et al 1983;Miwa et al 1980;Ishida et al 1981). PK deficiency causes an anemia, which is associated with null activity in Caucasians in homozygotes, and no disease, but intermediate enzyme levels in heterozygotes (Valentine, Tanaka and Miwa 1961).…”
Section: Activity Variants and Null Allelesmentioning
confidence: 99%
“…PK deficiency causes an anemia, which is associated with null activity in Caucasians in homozygotes, and no disease, but intermediate enzyme levels in heterozygotes (Valentine, Tanaka and Miwa 1961). In Japanese, at least seven different PK alleles with decreased activity have been identified (Miwa et al 1980). These alleles retain some PK activity, in contrast to the null allele found in Caucasians, and consequently family studies often do not indicate significant reduction of PK activity in either parent of an affected individual.…”
Section: Activity Variants and Null Allelesmentioning
confidence: 99%
“…In particular, it has become apparent that pyruvate kinase (PK) deficiency often shows either normal or increased red cell PK activity (Miwa et al 1980). The accumulation of red cell 2,3-diphosphoglycerate (2,3-DPG) and the decrease of adenosine-5'-triphosphate (ATP) are characteristically seen in most cases of PK deficiency.…”
mentioning
confidence: 99%